Lost landscapes of childhood: An ecostylistic analysis of The Issa Valley - Chrzanowska-Kluczewska Elżbieta (Journal of World Languages, 2022)
The Issa Valley, a novel by the renowned Polish émigré poet and writer Czesław Miłosz, is a partly autobiographical rendition of Miłosz’s early years spent on his family estate at Szetejnie in Lithuania. The omniscient narrator presents the early years and adolescence of a Polish gentry boy, Thomas Dilbin; the second, equally important protagonist of the novel is the eponymous Issa Valley. The book is an homage paid to the beauty of Lithuanian nature and to the world of childhood memories; as such, it invites an attempt at an ecostylistic interpretation, which is the main aim of this study. The methodology applied to analyze its English translation partly follows Geoffrey Leech and Mick Short’s taxonomy of linguistic aspects relevant when studying fiction, such as context, lexicon, syntax, and figuration. Furthermore, this ecostylistic analysis focuses on figuration and its imagistic potential in picturing the Issa landscape. Master tropes (simile, metaphor, synecdoche, irony, and antithesis) work at three textual levels: micro-, macro-, and megatropical. This scrutiny proves that the novel is an instance of what I call existential ecology, with antithesis as a dominant textual backbone; it also demonstrates that figuration reflects an intensely corporeal experience of nature by the young Thomas. The main contribution of this article to Miłosz’s scholarship is that it offers an ecostylistic reading of The Issa Valley, which has not been applied to the novel so far, specifically from lexical, grammatical, and tropological perspectives.